Clinical Teaching Sebagai Penangganan Disleksia Pada Peserta Didik - Sari, Mulia; Ulfa, Mariah; Hasanah, Uswatun (Transformasi Manageria Journal of Islamic Education Management, 2024)
Dyslexia is a term that is related to the pattern of learning difficulties of students and is accompanied by characteristic problems in word recognition and accuracy, poor decoding and weak spelling abilities. Dyslexia can be experienced by students at all levels of education. Dyslexia should not prevent students from getting learning like other students. Thus the teacher must find the right subscription to overcome the learning difficulties of dyslexic students. In compiling this article, the authors use qualitative research and focus on literature studies. The author collects through documentation activities, namely collecting all information about dyslexia in books, journals, theses and other reading sources. This study aims to determine the definition of dyslexia, the characteristics of dyslexia and the factors that can affect dyslexia. The author also aims to inform readers about dyslexia subscription assistance which is termed clinical teaching. This article shows that clinical teaching can be one of the subscriptions for dyslexic students to find the weaknesses they face so that teachers and parents can create learning that is in accordance withthe characteristics of dyslexia and they can increase the potential that exists in dyslexic students. Keywords: Dyslexia, Clinical Teaching, Students